AN ANALYSIS OF ENGLISH-INDONESIAN Translation Quality on Twitter Web Pages - Muhammad Awaluddin Kamil (Journal of English and Education, 2014)
This paper finds out the readers’ responses towards the quality of the translation in Twitter Web pages. A qualitative case study was employed in gaining the results of the study (Baxter and Jack, 2008; McMillan and Schumacher, 2003, cited in Syamsudin and Damayanti, 2007). The data were gained from the analysis of the translation quality supported by the translation procedures and an interview to five English students majoring Translation. The interview is intended to get which pages which are mostly visited by them and the opinions on the translation quality supporting the translation procedures theories. This study finds out that there are 170 phrases from 22 selected Twitter Web pages which were gained from the interviewees’ responses. The good characteristics of translation are achieved since the clarity and naturalness of the TL are maintained despite several improper translations. This research is expected that the translators, in relation to the characteristics of good translation, should create and choose natural and clear translation to achieve the goals to attain the real message of the text. Keywords: Translation, Translation Procedures, Twitter, Translation Quality